Answer: Option 1 is correct that is (m+5)(m-9)
Step-by-step explanation:
We can answer the given question from "Zero Product Property".
whenever we have have factors comes out to be suppose (x-2) we will equate it to zero and we get x= -2 hence in given question we have to write in the converse form
we can see if we will equate (m+5) = 0 then only we will get m = -5
and (m-9) =0 then only m = 9
So, its just that you have to take opposite sign inside the bracket that is given with the root.
Option 2,3 and 4 are incorrect because of the reason mentioned above.
Hence, Option 1 is correct